(untitled) (IIUC Studies, 2009)
John Osborne’s play Look Back in Anger created history in England when it was first staged on 8 May 1956. It depicts the disillusionment and rebelliousness of post-war youth in Britain. The suffering hero Jimmy Porter is the representative of this generation with nowhere to go. Having lost the war against society he fights for a place of his own in domestic relationships and dominates the action of the play. Though "Look Back in Anger is the one- man play per excellence." 1 Helena Charles, the friend of Jimmy’s wife Alison, makes her presence felt in spite of his dominance in the play by her guts who stands up to Alison’s defense. Later she falls to Jimmy’s bait easily, becomes something like his mistress and then leaves him and thus paves the way for a reconciliation between the husband and the wife. This paper aims at studying Helena’s arrival and departure and how do they contribute to the reunion of the estranged couple doi: 10.3329/iiucs.v4i0.2690 IIUC STUDIES Vol. - 4, December 2007 (p 41-48)